2021
DOI: 10.20884/1.jks.2021.16.3.1716
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Study of Muslim Nurses’ Experience During End-Of-Life Decision Making

Abstract: <p class="paragraph" align="center">ABSTRACT</p><p class="paragraph"><strong>Objectives</strong>: This study examines the significance of Muslim nurses' lived experiences in the Intensive Care Unit (ICU) when it comes to End-of-Life (EOL) decisions (ICU)</p><p class="paragraph"><strong>Methods</strong>: The research was carried out at an intensive care unit (ICU) of a government hospital in Central Java, Indonesia. Fourteen nurses were chosen as participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They also act as a guarantor of the rights of critical patients and assume responsibility for decisions related to their care and treatment (Padilla Fortunatti, 2014). The problems that arise would be related to making treatment decisions, as sometimes nurses cannot predict when the family will decide on the next treatment and how long they would need to wait until the family has made their decision (Hidayat et al, 2021). This study also found that most participants revealed that the decisions taken by the family will affect the continuity of care in patients and whether nursing actions will be continued or stopped.…”
Section: Discussionmentioning
confidence: 99%
“…They also act as a guarantor of the rights of critical patients and assume responsibility for decisions related to their care and treatment (Padilla Fortunatti, 2014). The problems that arise would be related to making treatment decisions, as sometimes nurses cannot predict when the family will decide on the next treatment and how long they would need to wait until the family has made their decision (Hidayat et al, 2021). This study also found that most participants revealed that the decisions taken by the family will affect the continuity of care in patients and whether nursing actions will be continued or stopped.…”
Section: Discussionmentioning
confidence: 99%